Correlation between physical and mechanical properties of mudrock - Lashkaripour, G. R. (Journal of Nepal Geological Society, 2000)
The paper describes the statistical relationship between physical and mechanical properties of mudrock. It focuses particularly on the correlation between index parameters that are relatively easy to measure and mechanical properties that are difficult to determine. Data for regression analysis were extracted from available published information. Moreover, many tests were carried out on different types of mudrock from various sites. Reasonably good correlation is found between some index parameters and mechanical properties, and various regression equations are proposed for predicting mechanical properties for available data. There is a good correlation between the point load, water content, porosity, and modulus of elasticity with the uniaxial compressive strength, whereas the correlation between the density, elastic wave velocity, and Poisson's ratio with the compressive strength is poor. Theses correlations may aid engineers to make preliminary estimation of the mechanical properties of mudrock when samples of adequate size for testing are generally not available. Furthermore, the selective use of proposed relationships may even reduce the testing requirements of specific projects.